2022
DOI: 10.1177/08853282221104175
|View full text |Cite
|
Sign up to set email alerts
|

Layered dermal reconstitution through epigallocatechin 3-gallate loaded chitosan nanoparticle within enzymatically crosslinked polyvinyl alcohol/collagen fibrous mat

Abstract: Biocompatible electrospun fiber comprising bioactive substrates has potential to implant into the wound site as a reliable therapeutic approach in tissue regeneration. Here, electrospun polyvinyl alcohol conjugated tyramine (PVA-Tyr) and collagen (Col) fibrous mat containing chitosan nanoparticle loaded with epigallocatechin 3-gallate (NCs-EGCG) developed and the composite was applied to evaluate in vivo wound healing ability of fabricated wound patch. The synthesized PVA-Tyr and Col were electrospun and cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…3,31 Contrary to this, various studies demonstrated the positive role of PVA in biomedical uses, benefits of PVA such as biocompatibility, anti-inflammatory and antimicrobial properties are consequential and cannot be ignored even if PVA shows less efficacy than other hemostatic agents. 32,33 In our study in the same way with previous studies, no cytotoxic effects of PVA were observed. And it can be a great advantage for using this material despite the unproven powerful effect.…”
Section: Discussionsupporting
confidence: 88%
“…3,31 Contrary to this, various studies demonstrated the positive role of PVA in biomedical uses, benefits of PVA such as biocompatibility, anti-inflammatory and antimicrobial properties are consequential and cannot be ignored even if PVA shows less efficacy than other hemostatic agents. 32,33 In our study in the same way with previous studies, no cytotoxic effects of PVA were observed. And it can be a great advantage for using this material despite the unproven powerful effect.…”
Section: Discussionsupporting
confidence: 88%
“…The ADSCs at 2 × 10 4 cells/well were seeded on hydrogel surfaces. The morphology, viability, and growth ability of seeded cells were monitored by microscopic observation, trypan blue exclusion dye assay, and water‐soluble formazan dye assay 3,4,8 …”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] These hydrogels are formed in different geometries, such as nanoparticle, microparticle, microcapsules, and microfibers. 3,4,8 Among these, the microparticles are commonly crosslinked physically through thermo-crosslinking and ionic-crosslinking strategies and chemically through photoinitiated or enzymatic polymerization approaches. 2,4,9 The physically crosslinked microparticles are easily undergo decomposition and swelling under physiological conditions and subsequently, their long-term mechanical stability is insufficient for cell or drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate tissue scaffolds have to provide biologically interactive microenvironment, mechanically durable and elasticized structure like native nerve tissue, and topographically biomimetic architecture, which would be feasible through combination of synthetic and natural biopolymers, since each one possesses speci c required properties [11][12][13][14]. Besides, the electrospinning technique has been used for manufacturing brous scaffolds composed of biopolymers and bioactive molecules, which is a favorable microenvironment from structural point of view for cell culture, drug loading, and tissue regeneration because of their similarity to the natural ECM architecture and their high surface-to-volume ratio [15][16][17].…”
Section: Introductionmentioning
confidence: 99%